Setreasure: Andoid-Based Learning Media on Sets Material - Ahmadah, Intan Fathimah; Risqi, Erlyanna Nur; Solehah, Mar'atus (UIN Walisongo Semarang, 2023)
This study aims to determine the feasibility of developing the SETREASURE learning media that has been developed and to determine the students' responses to the SETREASURE learning media. SETREASURE is aimed at seventh grade students, especially on set material. This research was conducted using the Research and Development method with the ADDIE development procedure (Analyze, Design, Development, Implementation, and Evaluation) using the Construct2 application and the web2apk. The data collection technique used a validation questionnaire in material validation sheets, media validation sheets, and student response questionnaires. The developed learning media application is equipped with material especially on in seventh grade. The feature of application, such as explanations, videos, sample questions, practice questions, and game score results.The data analysis technique in the form of an assessment score was carried out quantitatively. Based on the validation results of the learning media, SETREASURE is very feasible with a score of 83.33% on the material aspect and 81.67% on the media aspect with a note of slight improvement, as well as the results of the student response questionnaire were given a percentage of 83.21%. Students also gave a positive response to the SETREASURE learning media so that it can be stated that this learning media is very interesting for students.Keywords: Construct2, Learning Game, Mathematics Learning Media, Sets